Investigation of Formalin-Fixed Tissue Optical Characteristics in the Range of 200–500 GHz Using Pulsed Terahertz Reflection Spectroscopy to Differentiate Oral Malignant, Benign, and Cyst - Jenifer Isabella, S. Stella; Sunitha, K. A.; Magesh, K. T; Arjunan, Sridhar P.; Pesala, Bala (Journal of Spectroscopy, 2022)
The application of Terahertz electromagnetic waves to diagnose oral cancer was investigated. A single case of formalin-fixed oral squamous cell carcinoma (malignant), ameloblastoma (benign), and odontogenic keratocyst was examined using terahertz pulsed spectroscopy in the frequency span of 0.1–2 THz. The measured absorption coefficient, refractive index, and the extinction coefficient were reported to be high for malignant samples than benign and cyst. The THz results are validated with hematoxylin and eosin-stained microscopic images. The results demonstrate that the THz signal was shown to be consistently higher for the malignant sample compared to benign and the cyst. These results indicate that THz signals responded to the cell density by eliminating the effect of water.